Effects of wearing lower leg compression sleeves on locomotion economy - Kurz, E.; Anders, C. (Journal of Sports Sciences, 2018)
The purpose of this investigation was to assess the effect of compression sleeves on muscle activation cost during locomotion. Twenty-two recreationally active men (age: 25 ± 3 years) ran on a treadmill at four different speeds (ordered sequence of 2.8, 3.3, 2.2, and 3.9 m/s). The tests were performed without (control situation, CON) and while wearing specially designed lower leg compression sleeves (SL). Myoelectric activity of five lower leg muscles (tibialis anterior, fibularis longus, lateral and medial head of gastrocnemius, and soleus) was captured using Surface EMG. To assess muscle activation cost, the cumulative muscle activity per distance travelled (CMAPD) of the CON and SL situations was determined. Repeated measures analyses of variance were performed separately for each muscle. The analyses revealed a reduced lower leg muscle activation cost with respect to test situation for SL for all muscles (p < 0.05, Etap2 > 0.18). The respective significant reductions of CMAPD values during SL ranged between 4% and 16% and were largest at 2.8 m/s. The findings presented point towards an improved muscle activation cost while wearing lower leg compression sleeves during locomotion that have potential to postpone muscle fatigue.